The Relationship Between Helicobacter Pylori And Interleukin 1 Beta Level In Iraqi Patients With Diabetic And Thyroid Disorder - Methaq Hadi Lafta; Dr. Nowroz Dalirezh (Revista Electronica de Veterinaria, 2024)
The study was conducted on 88 influencers, 46 of whom were male, 42 samples from Haddith that were still present and still visible, diabetes, those infected with H. pylori, and uninfected persons, and their ages were between (35-70) years from )1/1/2023 - 1/1/2024( From Al-Diwaniyah General Hospital in Al-Diwaniyah Governorate, where numbers were collected from visitors and healthy people and were separated by the Central Croatian device, then the biochemical test was measured, which showed (Interleukin-1-beta, FBS, T3, T4, TSH).The results of the current research showed a significant increase in the levels of (Interleukin-1-beta, FBS.) in the blood serum of patients compared to the control group, with no significant differences in the levels of (T3, T4, TSH) in both groups, and at its level, the probability of P ≤ 0.05 .